Madrasah Head's Instructional Leadership Approach to the Development of New Teachers' Professionalism - Nur Efendi; Candra Wijaya (International Journal of Advanced Studies in Educational Management (IJASEM), 2025)
This research aims to explore the instructional leadership of madrasah principals in guiding young teachers at SMA Al-Muhafidzoh Blitar, with a focus on leadership roles and strategies, experiences and perceptions of young teachers, as well as the impact of leadership on student learning outcomes. Qualitative research methods are used with data collection techniques through in-depth interviews, observation and document analysis. The research results show that madrasa heads play a key role in establishing a clear educational vision and implementing strategies such as mentorship programs, regular training, and constructive feedback that are effective in improving young teachers' pedagogical and classroom management skills. Young teachers' experiences and perceptions of the guidance they receive are generally positive, with many stating that the support of madrasah principals is very helpful in increasing their self-confidence and competence, despite several challenges such as time constraints. The impact of instructional leadership on student learning outcomes is clearly visible by increasing academic performance and student engagement in the learning process. This research confirms the importance of effective instructional leadership in creating an educational environment that is conducive to the professional development of young teachers and improving the quality of student learning outcomes at SMA Al-Muhafidzoh Blitar. These findings can be a reference for developing leadership strategies in similar educational institutions